Recovery of Zirconium from Zircaloys Using a Hydrochlorination Process. (1st February 2021) - Borjas Nevarez, Rosendo; McNamara, Bruce; Poineau, Frederic
Abstract: For several decades, extensive research has been performed on the recovery and purification of zirconium from spent nuclear fuel cladding using a variety of chlorination reaction processes. After the reaction between fuel cladding and chlorine gas, zirconium tetrachloride is separated from other chloride species based on their boiling/sublimation points; however, the presence of iron and niobium chloride impurities limits the efficiency of these processes. In this work, chlorination products of Zr, Fe, and Nb mixtures were analyzed by thermogravimetric analysis, and the results suggest that Fe impurities cannot be removed via chlorination alone. Purification of zirconium from Zircaloy-2, Zircaloy-4, and a Zr-Nb alloy was performed via hydrochlorination using a sealed tube reaction system. The purity of the final ZrCl4 products is higher than 99.99% after successful removal of Fe and Nb.